(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2009)
Arsenic in water can do harm to human health. High arsenic concentrations have been reported recently from the USA, China, Chile, Bangladesh, Taiwan, Mexico, Argentina, Poland, Canada, Hungary, Japan and India. Conventional techniques used for arsenic removal involves oxidation, precipitation, membrane separation. The present study involves the removal of arsenic from wastewater by batch adsorption technique using bentonite. Bentonite contains montmorillonite which has the quality to adsorb inorganic and organic materials. Relying upon arsenic test strip method, the quantity of arsenic was determined after the treatment of 500 ppb arsenic solution with bentonite. Percentage adsorption was determined for bentonite-arsenic solution system as a function of i) contact time, ii) pH iii) temperature iv) mesh size and v) adsorbate dose. Maximum arsenic adsorption was observed at 20OC at pH 2 and 8. Minimum particle size favors maximum arsenic adsorption. The time taken to maintain equilibrium was 30 minutes. Bentonite is suitable for removal of arsenic from wastewater. Key words: Arsenic removal, Bentonite , Batch adsorption, Wastewater doi: 10.3329/bjsir.v44i1.2716 Bangladesh J. Sci. Ind. Res. 44(1), 81-86, 2009